2010
DOI: 10.4321/s1130-05582010000400005
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastoma multiquístico mandibular tratado con terapia menos invasiva: Caso clínico y revisión de la literatura

Abstract: El ameloblastoma es un tumor odontogénico benigno, localmente invasivo y recidivante, que constituye aproximadamente el 10% de los tumores odontogénicos. Estos tumores ocurren más frecuentemente en la mandíbula. El cuadro clínico se caracteriza generalmente por presentar deformaciones faciales, crecimiento lento y asintomático. El tratamiento depende del tipo, la localización y el tamaño del tumor, así como de la edad del paciente. En este artículo se presenta un caso de ameloblastoma multiquístico en la mandí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…As previously described, multicystic ameloblastoma is a lesion with a broad locally-infiltrative potential by growing trough spongy bone trabeculae, thus, treatment choice causes some controversies in literature. Hasegawa et al 20 (2013) defend that a conservative treatment for ameloblastoma, which consists in enucleating followed by lesion curettage, is considerable based in lower recurrence rate of 48.7%, what is still worrying, while most of studies has proposed surgical resections with a 1.5 cm clinically healthy bone margin, and showing recurrence rates for ameloblastomas treated by enucleation higher than 60%, 12,13 thus, in order to prevent any recurrence, treatment chosen for this case was the partial mandibulectomy, which was successful, once, as related before, healthy bone margins removed with the tumor histopathologic analysis showed no neoplastic tissue signals. In review by Gomes et al 21 (2006), authors reported that, generally, scientific community has tending to realize conservative surgical procedures, aiming to ensure the patient's quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described, multicystic ameloblastoma is a lesion with a broad locally-infiltrative potential by growing trough spongy bone trabeculae, thus, treatment choice causes some controversies in literature. Hasegawa et al 20 (2013) defend that a conservative treatment for ameloblastoma, which consists in enucleating followed by lesion curettage, is considerable based in lower recurrence rate of 48.7%, what is still worrying, while most of studies has proposed surgical resections with a 1.5 cm clinically healthy bone margin, and showing recurrence rates for ameloblastomas treated by enucleation higher than 60%, 12,13 thus, in order to prevent any recurrence, treatment chosen for this case was the partial mandibulectomy, which was successful, once, as related before, healthy bone margins removed with the tumor histopathologic analysis showed no neoplastic tissue signals. In review by Gomes et al 21 (2006), authors reported that, generally, scientific community has tending to realize conservative surgical procedures, aiming to ensure the patient's quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,11 The most accepted treatment for ameloblastoma is the surgical resection with a margin of healthy bone tissue, once studies has proved that, due to its locally-infiltrative behavior, multicystic ameloblastoma tumors treated by enucleation followed by curettage clearly tend to recur, while in lesions treated by surgical resection recurrence chances are fewer, since there is no remaining lesion tissue into the bone. 12,13 The aim of this paper is to present a multicystic ameloblastoma case on a female patient, occurring in the region of mandibular symphysis, which was treated by partial mandibulectomy.…”
Section: Wjdmentioning
confidence: 99%
“…Vários subtipos microscópicos de ameloblastoma convencional são reconhecidos, contudo, esses padrões têm pouca relação com o comportamento do tumor. Assim, o padrão folicular e plexiforme são os mais frequentes, e os menos comuns incluem: acantomatoso, de células granulares, desmoplásico e de células basais (LÓPEZ ALVARENGA, 2010, NEVILLE, 2016).…”
Section: Características Histopatológicasunclassified
“…It is a tumor derived from the residual epithelial components of tooth development, such as: remains of the dental lamina (Serres remains), reduced enamel epithelium, Malassez remains and the basal cells of the maxillary superficial epithelium [5]. In general, its appearance is manifested between the third to the seventh decade of life, except for the unicystic variety, which is diagnosed between the second and third decade, with no differences between the sexes (6). Its manifestation is more frequent in the mandible (85%) than in the upper jaw (15%).…”
Section: Introductionmentioning
confidence: 99%
“…Its manifestation is more frequent in the mandible (85%) than in the upper jaw (15%). In the mandibular location, the premolar, molar and ascending ramus of the mandible are more frequently affected, while in the upper jaw they are concentrated in the molar area, where they tend to extend to the maxillary sinus and the floor of the nostrils [6].…”
Section: Introductionmentioning
confidence: 99%